Gain Flatness and Noise Figure Optimization of C-Band EDFA in 16-channels WDM System using FBG and GFF - Chakkour Mounia; Aghzout Otman; Ait Ahmed Badiaa; Chaoui Fahd; Alejos Ana Vazquez; El Yakhloufi Mounir (Institute of Advanced Engineering and Science, 2017)
In this paper, Gain Flatness and Noise Figure of Erbium Doped Fiber Amplifier (EDFA) have been investigated in 16-channels Wavelength Division Multiplexing (WDM). Fiber Bragg Grating (FBG) is used in C-band with the aim to achieve flat EDFA output gain. The proposed model has been studied in detail to evaluate and to enhance the performance of the transmission system in terms of gain, noise figure and eye diagram of the received signals. To that end, various design parameters have been investigated and optimized, such as frequency spacing, EDF length and temperature. To enhance the transmission system performance in terms of gain flatness, the Gain Flattening Filter (GFF) has been introduced in the design. To prove the efficiency of the new design, the optical transmission system with optimized design parameters has been compared with a previous works in the literature. The simulation results show satisfactory performance with quasi-equalized gain for each channel of the WDM transmission system.